Concomitant dengue fever in Varicella zoster infection – a rare presentation - Shalihin, Mohd Shaiful Ehsan; Ahmad Radzi, Mohd Ashrafuddin; Osman, Iskandar Firzada (Malaysian Medical Association, 2019)
Varicella zoster infection is one of the self-limiting viral infections during childhood and dengue fever is an endemic infection in Malaysia, which commonly occurs in the form of nonspecific febrile illness at the initial stage. It is rare for the two viral infections to occur simultaneously. A case of dengue fever without warning sign in a five-year old girl was reported, with early symptoms of fever and vesicular rashes. She was clinically diagnosed with varicella zoster infection during the first visit. Surprisingly, she remained febrile even on day six of illness despite no new vesicular lesions on her skin. Due to suspicion of another infection, follow-up investigation was done and revealed isolated thrombocytopenia. This finding was confirmed with positive NS1Ag. A case of rare dengue fever concomitant with varicella zoster infection was reported.